PROSES PENYUSUNAN DAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA TELLULIMPOE KECAMATAN TELLULIMPOE KABUPATEN SINJAI - Kasrum, Kasrum; Khalik, Subehan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to determine the role of the village government in the preparation and realization of the use of the Village Revenue and Expenditure Budget in Tellulimpoe Village, Tellulimpoe District, Sinjai Regency. This research is a qualitative field research. The preparation of the Village Revenue and Expenditure Budget is carried out through juridical instruments in the form of village regulations, so that the mechanism and flow of its preparation have been clearly regulated through permendagri Number 20 of 2018. However, in substance, the preparation of the Village Revenue and Expenditure Budget in Tellulimpoe Village, Sinjai Regency has not fully implemented several basic principles, including the principles of need, transparency and participation. This problem also occurred at the realization stage, some programs with large enough budgets were delayed, making it quite detrimental because they could not be utilized optimally by the villagers.